Data collision and interference minimization in wireless sensor network using node data addressing with random access time - Nurulidayu Sainuddin,; Juwita Mohd Sultan,; Fakrulradzi Idris,; Mohd Azuani, (Penerbit Universiti Kebangsaan Malaysia, 2021)
A wireless sensor network (WSN) refers to a spatially dispersed network of sensors that monitor and collect environmental data and forward the collected data to the central station. WSN has been widely used in daily life and industrial applications, ranging from surveillance, military, healthcare, habitat monitoring, and agriculture application. However, WSN that uses radiofrequency (RF) communication may suffer from noise and interference caused by two or more radios that uses the same frequency. Data collision is also expected within the wireless network especially when numerous sensor nodes are transmitting their data to the base station (BS) through a shared medium. Hence, this research contributes in mitigating the RF interference and data collision in the network to increase the network’s data reliability by using the concept of Time Division Multiple Access (TDMA) protocol where each sensor node will be transmitting their data at a different time to avoid collision and interference in the shared medium. However, in this research, each sensor node will access the channel or the transmission medium at a random time. To prove the concept of the proposed method on data collision and interference minimization, an Internet of Things (IoT) based wireless sensor network for alerting application will be designed and implemented in the fire station. It has been found from the experimental result that RF interference and data reliability in the network can be reduced by 90% with the proposed algorithm by allowing the sensor node to access the RF channel and transmit the data at a random time.